Antimicrobial susceptibility, resistance determinants and molecular epidemiology of Neisseria gonorrhoeae in Ireland - RYAN, LAURA (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2019)
High-level resistance to and treatment failures with ceftriaxone and azithromycin, the first line agents for treatment of gonorrhoea are reported and antimicrobial-resistant N. gonorrhoeae is now an urgent public health threat. This study investigated rates of resistance to extended-spectrum cephalosporins (ESCs), azithromycin and other agents among gonococci in Ireland, resistance mechanisms and molecular epidemiology of the most resistant subset of isolates. Six-hundred and nine isolates from 4 different tertiary referral hospitals in Ireland were recovered for susceptibility testing against extended-spectrum cephalosprorins, azithromycin, ertapenem, ciprofloxacin, gemifloxacin, penicillin, tetracycline, spectinomycin, gentamicin and fosfomycin by gradient MIC strip. Forty-three isolates were selected for whole-genome sequencing based on elevated MICs, in particular to extended-spectrum cephalosporins and azithromycin. Sequencing libraries of N. gonorrhoeae genomic DNA were generated using the NexteraXTTM library preparation kit according to manufacturer?s instructions and sequenced on an Illumina MiSeq instrument. The NG-STAR database, pubMLST tool and ARG-ANNOT database were employed for data analysis. Seven high-level azithromycin resistant (HLAzi-R) isolates were identified, while no resistance to ceftriaxone was found. All isolates were susceptible to spectinomycin. 98.2%, 33% and 9.7% of isolates were non-susceptible to penicillin, ciprofloxacin and tetracycline, respectively. MIC90 for ertapenem, gemifloxacin, gentamicin and fosfomycin were 0.032 mg/L, 2 mg/L, 8 mg/L and 32 mg/L, respectively. Mosaic penA alleles XXXIV, X and non-mosaic XIII were associated with elevated ESC MICs. L421P mutation in ponA, G120K plus A121N/D/G alterations in penB (encoding PorB), H105Y alteration in mtrR and A deletions in the mtrR promoter were also associated with reduced susceptibility to ESCs. A2059G and C2611T mutations in 23s rRNA alleles were associated with HLAzi-R and gonococci with azithromycin MICs of 4-32 mg/L, respectively. The 43 isolates belonged to 31 NG-MAST STs and most prevalent MLST STs included ST1580, ST9396 and ST1901. All HLAzi-R isolates belonged to MLST ST1580, among which some clonal clustering was observed. When these isolates were compared to HLAzi-R isolates from a UK outbreak, analysed at a whole-genome sequence level, they differed significantly. This is the largest genomic study of Irish N. gonorrhoeae performed to date. Ceftriaxone remains a suitable empiric agent for treatment of gonorrhoea in Ireland. A number of potential alternative agents were identified. There was good correlation between previously described genetic mutations and phenotypic susceptibility categories for ESCs and azithromycin and N. gonorrhoeae. This work highlights the advantages and potential of whole-genome sequencing to be applied at scale in the surveillance of antibiotic resistant strains of N. gonorrhoeae, both locally and internationally.
APPROVED
Keywords: Neisseria gonorrhoeae